2005
DOI: 10.1080/07399330590905576
|View full text |Cite
|
Sign up to set email alerts
|

Interviews with Senegalese Commercial Sex Trade Workers and Implications for Social Programming

Abstract: The purpose of the study was to assess the efficacy of the Senegalese pubic policy toward registered sex workers through an interview process examining their backgrounds and evaluating their knowledge of sexual health. Sixty registered sex workers in Dakar, Senegal, were interviews at the Institute d'Hygiene Social (IHS) to investigate patient knowledge of contraceptives and sexually transmitted infections (STIs). Ninety-eight percent of the women reported that, as a result of their visits to the clinic, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 6 publications
2
26
0
Order By: Relevance
“…The economic consideration, however, may not be a rationale explanation for the gap among women who did not engage in commercial sex. Homaifar and Wasik (2005) found in their study that 24% of registered sex workers admitted to "never" using condoms with nonpaying partners, while 100% of them reported using condoms with their clients. This finding suggests that the relationship with their partners may partly explain the discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…The economic consideration, however, may not be a rationale explanation for the gap among women who did not engage in commercial sex. Homaifar and Wasik (2005) found in their study that 24% of registered sex workers admitted to "never" using condoms with nonpaying partners, while 100% of them reported using condoms with their clients. This finding suggests that the relationship with their partners may partly explain the discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies reviewed, the average age of sex workers mostly fell between 24 and 31 years, with estimates lower among urban sex workers in East African countries such as Ethiopia and Kenya [4,24] and higher averages recorded in Senegal [58,62,63], and some studies in Ghana (median 37 years [42]) and Kenya (mean 35 and 41.1 years [64,65]). Of concern, several studies documented the existence of very young sex workers: in the Congo, 28% of FSW in a cross-sectional study were between 14 and 18 years [66], and 33% had entered the sex industry before the age of 14.…”
Section: Age and Length Of Time In The Sex Work Industrymentioning
confidence: 95%
“…Most studies reported that between one and two-thirds of FSW were divorced or separated. In a large study in Senegal, 63% of sex workers were divorced and cited consequent economic factors and lack of occupational choice as reasons for entering sex work [58]. A study in Kenya found that half of the FSW interviewed who had ever moved residence had done so following divorce, either looking for work as a single woman, or trying to escape divorce-related stigma [59].…”
Section: Factors Promoting Entry To Sex Workmentioning
confidence: 98%
“…In Peru and in most settings with concentrated epidemics, high-risk groups have generally been limited to female sex workers or to special male groups (e.g. gay men, truck drivers, migrants, inmates) (Bronfman et al 2002;Gysels et al 2001;Homaifar and Wasik 2005;Kyrychenko and Polonets 2005;Mills et al 2001;Simooya et al 2001). In this study, two non-traditional high-risk groups, the esquineros and movidas were characterized after their identification through formative ethnographic work (Rosasco et al 2004;Salazar et al 2005).…”
Section: Discussionmentioning
confidence: 99%